Mittendrin? Lebenspläne und Potenziale älterer Menschen beim Übergang in den Ruhestand - Schneider, Norbert F.; Mergenthaler, Andreas; Staudinger, Ursula M.; Sackreuther, Ines (Beitrage zur Bevölkerungswissenschaft, 2014)
Older people today find themselves in a more favourable life situation than previous generations: Many of them have a high standard of living, a high level of education and good health. In view of this potential, the question arises as to what plans and ideas older people have today about living in the "third age". What decisions do they make in their transition to retirement with regard to further employment participation, civil society involvement or family support? This volume presents current findings from the interdisciplinary study "Transitions and Old Age Potential (TOP)" by the Federal Institute for Population Research on the life plans, potentials and transitions of 55- to 70-year-olds in Germany. In addition to presenting current scientific results, the volume aims to derive recommendations for action for politicians, companies and civil society organisations - and not least for the elderly themselves.